Монголчуудын им тамгын утга соёлын тухайд: On the Mongolians intangible culture about earmarks and brands - Тогтох (Mongolian Studies, 2023)
Above mentioned earmarks and brands have been used widely among Mongols as they symbolize profound meanings. There are numerous earmarks as well livestock brands with different shapes and forms. These various shaped earmarks and brands involve Mongols thinking of nature of worship and totem worship; also symbolize that peaceful life of people and livestock would be entrusted to blue heaven and earth and number of cattle be increased. This has been a form to be left the facts about Mongolians intangible culture.